Academic Senate Minutes 2002-04-25 - Academic Senate:::::::::
Agenda and minutes approved. Special guest Mayor Armando Flores. Candidates for graduation approved. Academic Calendar motion from Structures & Functions approved. First reading of EMT report from EPC. First reading of resolution Regarding Recruitment of an Underrepresented Group from SAC. FSAC ranking policy statement introduced, but discussion deferred to next meeting. Reports from President, Associated Students, APC and SAC. Good of the Order items from Steve Wilson and Bernie Goldstein.